Combined microwave and convection cooking increases post-cooking temperature rise of beef Biceps femoris muscles more than convection cooking - A. Gaschler; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 2012)
Combined microwave and convection cooking has gained popularity in the last 20 years because of more accurate heat control and more efficient use of energy. Combination microwave/convection cooking allows for more rapid cooking, but it does not have the same even heat distribution as convection cooking. Cooking is a critical stage when preparing meat. The main factors to consider during cooking are: temperature on the surface of meat, internal temperature throughout, and the method of heat transfer. Temperature on the surface and method of heat exchange primarily affect surface color and aroma, whereas internal temperature affects protein structure and flavor as well as aroma. At any temperature above 230°F, Maillard browning reactions start to occur and give meat its typical brown, caramelized appearance; however, high humidity prevents Maillard browning from occurring and dilutes flavor and odor components. All sensory attributes can, therefore, be significantly influenced by the cooking technique used. Different cooking methods allow for tenderness, flavor development, and color changes, all of which can be either acceptable or unacceptable for consumers. Different cuts of beef are cooked using different cooking methods to ensure that even a low-quality cut of meat can be acceptable for consumption. The objectives of our study were to investigate the differences between convection cooking and a combination of microwave and convection cooking and endpoint temperatures to observe how these factors affect post-cooking temperature rise, cooking yields, and tenderness.
Keywords: Cattlemen& #x27; s Day; 2012; Kansas Agricultural Experiment Station contribution; no. 12-231-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1065; Beef Cattle Research; 2012 is known as Cattlemen& #x27; s Day; Beef; Temperature; Biceps femoris; Microwave; Convection cooking; Cooking yields